Modeling the Human Placenta to Investigate Viral Infections During Pregnancy - Sheridan, Megan A.; Zhou, Jie; Franz, Alexander W. E.; Schust, Danny J. (Frontiers in Virology, 2022)
Throughout gestation, the placenta is vital for proper development of the fetus. Disruptions in trophoblast, the main functional cell type of the placenta, stress the pregnancy, with potential adverse outcomes for both mother and baby. While the placenta typically functions as an effective pathogen barrier to protect the fetus, there are scenarios in which viral infections either cross the placenta or disturb its function. Here, we briefly review placental morphologic and functional changes across pregnancy and how these relate to routes for and protection from pathogens. We then explore the potential advantages and limitations of the current primary trophoblast models (primary cultures/explants, cell lines, trophoblast stem cells and trophoblast organoids) and stem cell-derived trophoblast models (naïve and primed embryonic stem cells [ESCs], and blastoids) and discuss these in the context of what is already known about (1) how viruses cross the placenta and the mechanisms that are used for its protection and (2) how these protective mechanisms change across gestation.